“The Context Required It”: Pandemic, Teacher Agency and Inclusion in Chile; [“El Contexto Te Lo Requiere”: Pandemia, Agencia Docente E Inclusión en Chile] - Herrera-Seda, C (Pontificia Universidad Catolica de Valparaiso, 2023)
The outbreak of the pandemic in 2020 represented one of the greatest educational challenges of recent times, making the goal to achieve inclusive education even more challenging. In Chile, schools had various initiatives to address distance learning in a context of social inequity. The present study sought to understand how teachers agency for inclusion was developed in a Chilean school. A mixed parallel design was used, using a self-reported questionnaire by teachers to go deep into the changes made, and a group interview to delve into the institution organization. Among the results, actions that sought to adapt the traditional to the new educational context under the idea of reaching all students from the emotional bond stand out. These changes are mostly made among teachers, based on relationships of trust and emotional support in the absence of institutional support. The results presented contribute to broaden the understanding of teachers agency for inclusion in the context of the COVID crisis, opening questions for the approach of the subject in the context of face-to-face teaching. © 2023 Pontificia Universidad Catolica de Valparaiso. All rights reserved.